Amphibians and Reptiles recorded at Batu Apoi, a lowland dipterocarp forest in Brunei Darussalam - Das, I. (National University of Singapore, 1995)
An inventory of amphibians and reptiles, made at the Batu Apoi Forest Reserve, Temburong District, Negara Brunei Darussalam, based on collections and observations made between 1992-1993, is presented. A total of 94 species of amphibians and reptiles have been recorded, including 50 species of amphibians and 44 species of reptiles. Poorly-known and probably rare species recorded at the site include the microhylid frog kalophrynus intermedius and the colubrid snake ophisthotropis typicus. The problems of sampling in architecturally complex sites such as rainforests are discussed, and long term sampling programmes have been favoured.